Pemanfaaatan Kebun Biologi Sebagai Media Pembelajaran - Taib, Eva Nauli (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2012)
The use of instructional media in teaching-learning process can help generate students’ interests and help motivate students. This study aims to determine whether the use of natural media such as Angiospermae plants from the biological gardens can improve students’ mastery and learning outcomes and to find students’ responses toward the use of natural media as learning media. This research was conducted as a continuation of a previous study conducted at the State Junior High School (SMP Negeri) 2 of Lhoong Aceh Besar. This research employed pre-experimental method which only used one class. The instruments used were pretest and posttests, student worksheets, the lesson plans and student response sheets. The results of the pretest and posttest which were analyzed by t-test reveals that the use of natural media from Seungko Mulat biological gardens can improve student learning outcomes. The test results of 22 students are for individual learning mastery, 84.62% for classical mastery, and the students’ responses toward the use of biological garden are positive.